Data Associated with "Logjam Characteristics as Drivers of Transient Storage in Headwater Streams" - Marshall, Anna; Zhang, Xiaolang; Sawyer, Audrey Hucks; Wohl, Ellen; Singha, Kamini (Colorado State University. Libraries, 2022)
Logjams in a stream create backwater conditions and locally force water to flow through the streambed, creating zones of transient storage within the surface and subsurface of a stream. We investigate the relative importance of logjam distribution density, logjam permeability, and discharge on transient storage in a simplified experimental channel. We use physical flume experiments in which we inject a salt tracer, monitor fluid conductivity breakthrough curves in surface water, and use breakthrough-curve skew to characterize transient storage. We then develop numerical models in HydroGeoSphere to reveal flow paths through the subsurface (or hyporheic zone) that contribute to some of the longest transient-storage timescales. In both the flume and numerical model, we observe an increase in backwater and hyporheic exchange at logjams. Observed complexities in transient storage behavior may depend largely on surface water flow in the backwater zone. As expected, multiple successive logjams provide more pervasive hyporheic exchange by distributing the head drop at each jam, leading to distributed but shallow flow paths. Decreasing the permeability of a logjam or increasing the discharge both facilitate more surface water storage and elevate the surface water level upstream of a logjam, thus increasing hyporheic exchange. Multiple logjams with low permeability result in the greatest magnitude of transient storage, suggesting that this configuration maximizes solute retention in backwater zones, while hyporheic exchange rates also increase. Understanding how logjam characteristics affect solute transport through both the channel and hyporheic zone has important management implications for rivers in forested, or historically forested, environments.
This repository contains data for the experimental flume and numerical model runs referenced in Marshall et al., 2022. Source code, data csv files for statistical analysis, and calculated temporal moments are included.
Department of Geosciences
Keywords: fluvial geomorphology; logjams; large wood; transient storage; hyporheic exchange